Associations of cystatin C with incident chronic kidney disease and all-cause mortality in patients with normal glucose tolerance and prediabetes - Guan-Hong Lin; Ching-Heng Lin; Jun-Sing Wang (Scientific Reports)
Abstract We investigated the association of cystatin C with incident chronic kidney disease (CKD), defined as an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m2. We enrolled patients with an eGFR ≥ 60 mL/min/1.73 m2 who underwent an oral glucose tolerance test (OGTT) between 2011 and 2013. Patients with diabetes were excluded from the analysis. We measured their cystatin C levels, and all patients’ renal function and survival status were followed until March 2023. Cox-proportional hazard models were conducted to examine the association of cystatin C with incident CKD and all-cause mortality. A total of 146 patients were analyzed. After a median follow-up period of 10.7 years, patients with a higher cystatin C (≥ median vs. < median) were independently associated with a higher risk of incident CKD and all-cause mortality (adjusted hazard ratio [HR] 2.96, 95% CI 1.09 to 8.09, p = 0.034). The findings were consistent when cystatin C was analyzed as a continuous variable. The association was mainly observed in patients with prediabetes (adjusted HR 5.75, 95% CI 1.34 to 24.69, p = 0.019). In summary, a higher cystatin C was independently associated with risk of incident CKD and all-cause mortality in non-diabetes patients with an eGFR ≥ 60 mL/min/1.73 m2.